COLLECTION THINKING : within and without libraries,archives and museums - Camlot, Jason, 1967-; Langford, Martha; Morra, Linda M. ([S.l.] : ROUTLEDGE, 2023)
Collection Thinking is a volume of essays that thinks across and beyond critical frameworks from library, archival, and museum studies to understand the meaning of "collection" as an entity and as an act. It offers new models for understanding how collections have been imagined and defined, assembled, created, and used as cultural phenomena. Featuring over 70 illustrations and 21 original chapters that explore cases from a wide range of fields, including library and archival studies, literary studies, art history, media studies, sound studies, folklore studies, game studies, and education, Collection Thinking builds on the important scholarly works produced on the topic of the archive over the past two decades and contributes to ongoing debates on the historical status of memory institutions. The volume illustrates how the concept of "collection" bridges these institutional and structural categories, and generates discussions of cultural activities involving artifactual arrangement, preservation, curation, and circulation in both the private and the public spheres. Edited and introduced collaboratively by three senior scholars with expertise in the fields of literature, art history, archives, and museums, Collection Thinking is designed to stimulate interdisciplinary reflection and conversation. This book will be of interest to scholars and practitioners interested in how we organize materials for research across disciplines of the humanities and social sciences. With case studies that range from collecting Barbie dolls to medieval embroideries, and with contributions from practitioners on record collecting, the creation of sub-culture archives, and collection as artistic practice, this volume will appeal to anyone who has ever wondered about why and how collections are made.
Keywords: Collection development (Libraries); Collectors and collecting